2019
DOI: 10.1007/s40121-019-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Molecular Epidemiology of CTX-M-9 Group Producing Enterobacteriaceae Infections in Children

Abstract: Introduction The pandemic of extended-spectrum beta-lactamase-(ESBL)-producing Enterobacteriaceae (Ent) is strongly linked to the dissemination of CTX-M-type-ESBL-Ent. We sought to define the epidemiology of infections in children due to an emerging resistance type, CTX-M-9-group-producing-Ent (CTX-M-9-grp-Ent). Methods A retrospective matched case-control analysis of children with CTX-M-9-grp-Ent infections who received medical care at three Chicago area hospitals was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…1), we discovered that compared to living in a reference region (West Chicago, region 4), residence in South and Southwest Chicago (regions 5 and 6) was associated with a 5-times-higher MDR-Ent infection risk. Conversely, residence in Central and Northwest Chicago (regions 1 and 2) was linked to a Ͼ80% decreased infection risk (9,10). We also found that the majority of the highest-risk zip codes for MDR-Ent infection within the high-risk regions were in close proximity to area waterways (Fig.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…1), we discovered that compared to living in a reference region (West Chicago, region 4), residence in South and Southwest Chicago (regions 5 and 6) was associated with a 5-times-higher MDR-Ent infection risk. Conversely, residence in Central and Northwest Chicago (regions 1 and 2) was linked to a Ͼ80% decreased infection risk (9,10). We also found that the majority of the highest-risk zip codes for MDR-Ent infection within the high-risk regions were in close proximity to area waterways (Fig.…”
supporting
confidence: 52%
“…Mcr-1 (colistin) was found in A2 to A4, and QnrS, OqxA/B (quinolone), and bla OXA /bla AmpC (beta-lactam) were found in A1 to A4. Through culture-based methods (Table 1), 15 viable E. coli, Klebsiella pneumoniae, and Enterobacter cloacae isolates from A2 to A4 were found to harbor transmissible ARGs that were also detected in clinical isolates recovered from children residing in the high-risk region, including bla CTX-M-9grp , bla CTX-M-1grp , bla SHV-ESBL , and bla CMY-AmpCs , along with additional aminoglycoside and quinolone ARGs (7,9,10). Sixty percent of culture isolates were resistant to three or more antibiotic classes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most bacterial species within the Enterobacter genus are commonly found in human and animal intestines. Only a few Enterobacter species have been identified as conditional pathogens and have been described to cause extra‐intestinal and invasive infections in humans (Logan et al, ; Logan, Renschler, Sumanth, Weinstein, & Ramanan, ; Lukac, Bonomo, & Logan, ; Mogle, Beccari, Steele, Fazili, & Kufel, ). In aquaculture, the pathogenicity of Enterobacter has been reported relatively infrequently.…”
Section: Discussionmentioning
confidence: 99%